High energy transmission micro-beam Laue synchrotron X-ray diffraction - Hofmann, F; Song, X; Jun, T; Abbey, B; Peel, M; Daniels, J; Honkimäki, V; Korsunsky, A (Elsevier, 2010)
Synchrotron-based micro-beam Laue diffraction is an experimental technique for the study of intra-granular lattice orientation and elastic strain in individual crystallites of polycrystalline engineering alloys. Traditionally the technique operates in reflection geometry with a polychromatic X-ray beam focused to a sub-micron spot and with photon energy ranging from approximately 5 to 30 keV. This allows the study of material in the near-surface region. In this paper the first feasibility study of extending this technique to a polychromatic beam with significantly higher photon energies from 50 to 300 keV is presented. At these energies, transmission through even thick samples can be achieved and it becomes possible to study deeply buried material volumes. The technique is demonstrated by recording an orientation map of a flat dogbone large-grained Ni sample. Comparison with an optical micrograph shows very good agreement, validating the feasibility of this approach.